2018
DOI: 10.1111/andr.12489
|View full text |Cite
|
Sign up to set email alerts
|

The role of neutrophil‐to‐lymphocyte ratio in men with erectile dysfunction—preliminary findings of a real‐life cross‐sectional study

Abstract: The aim of this study was to investigate the role of systemic inflammation by means of the neutrophil-to-lymphocyte ratio (NLR) in men with erectile dysfunction (ED). Complete demographic, clinical, and laboratory data from 279 consecutive men with newly diagnosed ED were analyzed. Health-significant comorbidities were scored with the Charlson Comorbidity Index (CCI). A complete blood count was requested for every man, and the NLR was calculated for every individual. Patients were invited to complete the IIEF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…Therefore, NLR is better to indicate the impact of these two white blood cell subgroups than focusing on neutrophil alone (Azab et al, 2010). Likewise, our findings (Ventimiglia et al, 2018). Another study demonstrated that systemic inflammation negatively affects the possibility of sperm retrieval in TESE (Yucel et al, 2017).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Therefore, NLR is better to indicate the impact of these two white blood cell subgroups than focusing on neutrophil alone (Azab et al, 2010). Likewise, our findings (Ventimiglia et al, 2018). Another study demonstrated that systemic inflammation negatively affects the possibility of sperm retrieval in TESE (Yucel et al, 2017).…”
Section: Discussionsupporting
confidence: 84%
“…Ventimiglia et al . reported that NLR decreases as a function of increasing ED severity and NLR > 3 as the most informative cut‐off for identifying men with severe ED (Ventimiglia et al ., ). Another study demonstrated that systemic inflammation negatively affects the possibility of sperm retrieval in TESE (Yucel et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations